2020
DOI: 10.19044/esj.2020.v16n15p20
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Information Security Awareness and Practices among Third Level Education Staff, Case Study in Nalut Libya

Abstract: The development of Information and Communication Technologies (ICTs) is becoming very common throughout society. Therefore, it is a must to protect information assets. In addition to the technological aspect, research continues to confirm the need to enhance security awareness among employees. The objective of this study is to investigate the factors that may impact users' practice and awareness both in the workplace. Specifically, factors such as policy, behavior, training, knowledge of IT and education were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Relevant studies in the field have shown promising results. For instance, a study [26] observed a significant improvement in employees' cybersecurity awareness following the implementation of knowledge transfer and targeted training sessions focused on cybersecurity. Another study [27] established a positive correlation between organizational policies, employee behavior, training initiatives, IT knowledge, and education, all contributing to heightened security awareness and practices among employees.…”
Section: H Challenges Opportunities and Recommendationsmentioning
confidence: 99%
“…Relevant studies in the field have shown promising results. For instance, a study [26] observed a significant improvement in employees' cybersecurity awareness following the implementation of knowledge transfer and targeted training sessions focused on cybersecurity. Another study [27] established a positive correlation between organizational policies, employee behavior, training initiatives, IT knowledge, and education, all contributing to heightened security awareness and practices among employees.…”
Section: H Challenges Opportunities and Recommendationsmentioning
confidence: 99%
“…The success of information security depends on a suitable information security practice by the end users, the weakness in user security practices constitutes a larger threat to an organization's security more than any weakness in information security, therefore, the biggest challenge in information security are to transform users from the weakest line to the defense line by enhancing security practices (Rhee et al, 2009;Asker and Tamtam, 2020). According to Huang et al, (2011), the users could be the biggest vulnerability in information systems security, even with several security methods.…”
Section: Introductionmentioning
confidence: 99%
“…The weakness in user security practices constitutes a larger threat to an organization's security than any weakness in information security. Therefore, the biggest challenge in information security is to transform users from the weakest link to the defense line by enhancing security practices (Rhee et al, 2009;Asker and Tamtam, 2020). According to Huang et al (2011), users could be the biggest vulnerability in information systems security, even with several security methods in place.…”
Section: Introductionmentioning
confidence: 99%